Investigating Young Learners' Perceptions of Using E-Modules as a Learning Medium: A Mixed Methods Study - Bachrudin, Saeful; Drajati, Nur Arifah; Santosa, Eka Budhi (Social, Humanities, and Educational Studies (SHES): Conference Series, 2023)
The use of electronic modules (e-modules) in the teaching and learning pro-cess allows teachers to solve learning problems and strengthen learners' crea-tivity. E-modules often utilize digital multimodal modes of delivery to create meaningful learning. Through a mixed-methods research design, this study aimed to explore the perceptions of using e-modules as learning media among 24 learners. Questionnaires and interviews were used to collect data. A Likert scale was used to analyze the data from the questionnaire, while the interview data was qualitatively analyzed. The results of the questionnaire showed that 81.25 percent of young learners strongly agreed and 18.75 per-cent agreed to use e-modules as learning media. This research shows that the use of e- modules as learning media is perceived to support young learners' learning processes positively. Then, the interview results show that multimo-dality-based e-modules can increase young learners' learning motivation and are suitable as learning media. This research further implies that the use of e-modules can be used as a tool to improve learners' competence. In the con-text of teaching, e- modules offer flexibility of use in various teaching and learning settings, not limited to online settings.